Highly Al-doped TiO2 nanoparticles produced by Ball Mill Method: structural and electronic characterization. (October 2015) - de los Santos, Desireé M.; Navas, Javier; Sánchez-Coronilla, Antonio; Alcántara, Rodrigo; Fernández-Lorenzo, Concha; Martín-Calleja, Joaquín
Graphical abstract: Highlights: Highly Al-doped TiO2 nanoparticles were synthesized using a Ball Mill Method. Al doping delayed anatase to rutile phase transformation. Al doping allow controlling the structural and electronic properties of nanoparticles. Abstract: This study presents an easy method for synthesizing highly doped TiO2 nanoparticles. The Ball Mill method was used to synthesize pure and Al-doped titanium dioxide, with an atomic percentage up to 15.7 at.% Al/(Al + Ti). The samples were annealed at 773 K, 973 K and 1173 K, and characterized using ICP-AES, XRD, Raman spectroscopy, FT-IR, TG, STEM, XPS, and UV–vis spectroscopy. The effect of doping and the calcination temperature on the structure and properties of the nanoparticles were studied. The results show high levels of internal doping due to the substitution of Ti 4+ ions by Al 3+ in the TiO2 lattice. Furthermore, anatase to rutile transformation occurs at higher temperatures when the percentage of doping increases. Therefore, Al doping allows us to control the structural and electronic properties of the nanoparticle synthesized. So, it is possible to obtain nanoparticles with anatase as predominant phase in a higher range of temperature.